2003
DOI: 10.1093/nar/gkg662
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of components of the pre-replication complex of Archaeoglobus fulgidus

Abstract: The eukaryotic pre-replication complex is assembled at replication origins in a reaction called licensing. Licensing involves the interactions of a variety of proteins including the origin recognition complex (ORC), Cdc6 and the Mcm2-7 helicase, homologues of which are also found in archaea. The euryarchaeote Archaeoglobus fulgidus encodes two genes with homology to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
63
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 29 publications
8
63
1
2
Order By: Relevance
“…However, in contrast with our results, the A. fulgidus Cdc6 factor was found to displace MCM hexamers bound to these DNA molecules (21). It is interesting to note that in a recent sequence analysis of the Cdc6-like proteins from various archaeal species, SsoCdc6-2 and the above A. fulgidus Cdc6 factor were reported to belong to different phylogenetic clades, thus being likely that they may play different roles at the replication origins (22).…”
Section: Figcontrasting
confidence: 99%
“…However, in contrast with our results, the A. fulgidus Cdc6 factor was found to displace MCM hexamers bound to these DNA molecules (21). It is interesting to note that in a recent sequence analysis of the Cdc6-like proteins from various archaeal species, SsoCdc6-2 and the above A. fulgidus Cdc6 factor were reported to belong to different phylogenetic clades, thus being likely that they may play different roles at the replication origins (22).…”
Section: Figcontrasting
confidence: 99%
“…Although all proteins are homologous, they appear to aggregate differently. Although the mtMCM appears to form double hexamers (10 -13), the enzymes from S. solfataricus (16), A. fulgidus, and Aeropyrum pernix (18) are hexamers. Electron micrograph reconstruction of mtMCM revealed ring-shaped hexamers (20) or heptamers (21), but no dodecamers could be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies with the MCM proteins of Methanothermobacter thermautotrophicus (mt) (10 -15), Sulfolobus solfataricus (16,17), and Archaeoglobus fulgidus (18) revealed that the enzymes possess biochemical properties similar to those of the eukaryotic Mcm4,6,7 complex: 3Ј 3 5Ј helicase, ssDNA binding, and DNA-dependent ATPase activity plus double-stranded (ds) DNA translocation.…”
mentioning
confidence: 99%
See 2 more Smart Citations